Effect of Laser-Irradiation on Photosynthetic Efficiency of Safflower Leaves - J.K. Pandey2; R. Gopal2,3, G. Kumar1, Preeti Srivastava1* (Journal of Phytology, 2010)
The present investigation has been undertaken to determine the influence of laser light at a wavelength of 632.8 nm on safflower leaves. Our study illustrates that non-irradiated plants possessed higher amount of chlorophyll (a+b) and carotenoid content as compared to irradiated plants. However a significant increase in total chlorophyll (Chl) content has been noticed on increasing the treatment duration from Â½ h to 1Â½ h. This increase in photosynthetic efficiency can also be measured by calculating the peak ratio (F685/F735 ratio) through LICF (Laser induced chlorophyll fluorescence) study. This ratio is dependent on the chlorophyll content of the leaves. It decreases with increase in chlorophyll content. Thus this method could be successfully deployed to measure change in photosynthetic activity of leaves and that too in a non-destructive manner. From our study it can be concluded that the mutagenic effectiveness of laser rays decreased with the increase in treatment dose.